A Critical Appraisal of Probiotics for Mastitis Control - Rainard, Pascal; Foucras, Gilles (Frontiers in Veterinary Science, 2018)
The urge to reduce antimicrobials use in dairy farming has prompted a search for alternative solutions. As infections of the mammary gland is a major reason for antibiotic administration to dairy ruminants, mammary probiotics have recently been presented as a possible alternative for the treatment of mastitis. To assess the validity of this proposal, we performed a general appraisal of the knowledge related to probiotics for mammary health by examining their potential modes of action and confronting these mechanisms to the immunobiology of mammary gland infections. Then we analyzed the literature published on the subject, taking into account the preliminary in vitro experiments and the in vivo trials. From this analysis, it appears that currently there is no sound scientific foundation for the use of probiotics to prevent or treat mastitis. We conclude that the prospects for oral probiotics are not promising, those for intramammary probiotics should be considered with caution, but that teat apex probiotics deserve further research.